2021
DOI: 10.1037/dev0001175
|View full text |Cite
|
Sign up to set email alerts
|

Approach-avoidance conflict and shyness: A developmental investigation.

Abstract: One long-standing theoretical model of shyness proposes that the origins and maintenance of shyness are associated with an approach-avoidance motivational conflict (Asendorpf, 1990), such that shy individuals are motivated to socially engage (high approach motivation) but are too anxious to do so (high avoidance motivation). However, this model has not been empirically tested in predicting the development of shyness. In two separate longitudinal studies, we used the Carver and White (1994) Behavioral Inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 53 publications
(107 reference statements)
4
15
2
Order By: Relevance
“…Contrary to Hypothesis 1, we found that, on average, shyness decreased from age 10 to 16; although we did find the predicted individual differences in shyness trajectories. The observed decrease in shyness is not consistent with research and theory on adolescence that highlights increases in self-consciousness and heightened sensitivity to peer evaluation, both of which seem likely to increase shyness (Cheek et al, 1986;Hassan et al, 2021). However, our findings are consistent with a few previous studies that have found mean-level decreases in shyness across adolescence (Barzeva et al, 2019;Laceulle et al, 2012;Zohar et al, 2019).…”
Section: Mean-level Changecontrasting
confidence: 92%
See 3 more Smart Citations
“…Contrary to Hypothesis 1, we found that, on average, shyness decreased from age 10 to 16; although we did find the predicted individual differences in shyness trajectories. The observed decrease in shyness is not consistent with research and theory on adolescence that highlights increases in self-consciousness and heightened sensitivity to peer evaluation, both of which seem likely to increase shyness (Cheek et al, 1986;Hassan et al, 2021). However, our findings are consistent with a few previous studies that have found mean-level decreases in shyness across adolescence (Barzeva et al, 2019;Laceulle et al, 2012;Zohar et al, 2019).…”
Section: Mean-level Changecontrasting
confidence: 92%
“…We found moderate to high rank-order stability of shyness from age 10 to 16, which is comparable to past longitudinal research examining rank-order stabilities in self-reported (Hassan et al, 2021;Zohar et al, 2019) and mother-reported shyness (Brandes et al, 2020;Karevold et al, 2012;Laceulle et al, 2012). For all time intervals, child self-reports were less stable than mother-reports.…”
Section: Rank-order Stabilitysupporting
confidence: 79%
See 2 more Smart Citations
“…There are several different theoretical perspectives on the origins and maintenance of shyness. One hypothesis is that shyness arises from an approach-avoidance motivational conflict (Asendorpf, 1990; Coplan et al, 2004; Schmidt & Buss, 2010; although see Hassan et al, 2021). Another hypothesis is that temperamental aspects of shyness (e.g., behavioral inhibition) may be linked to individual differences in the excitability of the central nucleus of the amygdala (e.g., Kagan, 1994; 1999); a brain area involved in threat sensitivity (LeDoux, 1996; Nader & LeDoux, 1999).…”
mentioning
confidence: 99%